The separation of ribonucleic acids from Escherichia coli on lysin-agarose. - Jones, D S (1976)
Lysine-agarose provides a simple means of separating RNA species of different moleecular weight. When RNA from Escherichia coli is added to a small column of lysine-agarose and elution is carried out at neutral pH with a shallow linear gradient of NaCl the RNA species are eluted according to size; 4S and 5S RNA species are completely separated and after a delay the 16S and 23S species are eluted as separate peaks. The process is very reproducible and the different species are eluted at a fixed salt concentration even when changes are made in the gradient, provided other conditions, under which the column is run remain constant.